Flexible Mixed Plastic Polypropylene Blend (PP-flex)
A mixed plastic polypropylene blend with tailored properties addresses the challenges of recycling and material quality, achieving improved flexibility and meeting stringent application requirements for flexible films and other products.
Patent Information
- Application Number
- JP2024560703
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-29
- Filing Date
- 2023-04-27
- Publication Date
- 2025-05-02
AI Technical Summary
The challenge lies in developing a polypropylene blend that closely mimics virgin resin properties, particularly for flexible applications like films, while addressing the difficulties in recycling due to factors like high pollution levels, dark color, odors, and emissions from polypropylene packaging waste.
A mixed plastic polypropylene blend with specific properties, including a density below 924 kg/m³, a soluble fraction content between 3.0% to 12.0% by weight, an ethylene-propylene rubber content less than 7.0% by weight, and an intrinsic viscosity range of 1.10 to 1.50 dl/g, is developed. This blend is designed to improve flexibility and meet the stringent requirements of flexible end-use applications.
The developed polypropylene blend exhibits improved flexibility, enabling its use in demanding applications, and meets the quality standards required for flexible films and other products, thus addressing the challenges of recycling and material properties.
Smart Images

Figure 2025514049000001 
Figure 2025514049000002 
Figure 2025514049000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to flexible mixed plastic polypropylene blends that are typically derived from recycled materials. [Background technology]
[0002] Polyolefins, particularly polyethylene and polypropylene, are increasingly being consumed in large quantities in a wide range of applications, including packaging for food and other products, textiles, automotive parts, and a wide variety of manufactured goods. Flexible polypropylene packaging products, and therefore waste products containing these systems, are generally heavily printed, often metallized, small in size, and in contact with biological contaminants. These attributes result in high contamination levels, dark colors, odors, and emissions, making mechanical recycling difficult. Film applications, in particular, require high-quality grades, placing strict demands on the inherent material properties of recycled materials.
[0003] Many attempts have been made to purify recycle streams derived from post-consumer garbage / waste. Among these methods, washing, sieving, aeration, etc. may be mentioned. For example, International Publication No. 2018046578 discloses a process for producing polyolefin recycle from mixed colored polyolefin waste, including packaging waste, which involves cold washing the waste with water, followed by washing with an alkaline medium at 60°C, followed by flake color sorting to receive a color-sorted (white, clear, other colors) monopolyolefin-rich fraction. These fractions are then treated at 50-155°C. U.S. Patent No. 5,767,230A describes a process that involves contacting PCR polyolefin chips containing volatile impurities with heated gas at a superficial velocity sufficient to substantially reduce volatile impurities, such as odor-active substances. However, to date, the market is actively seeking recycled materials with characteristics as close as possible to virgin resin. The main applications of flexible polypropylene recyclates could be cast and BOPP film applications, furniture decorative films, tapes, labels, or additives for injection molding applications to adjust properties, or base materials for peroxide-modified grades. Color remains a remaining challenge that has not been fully addressed. There is a particular need for recyclates suitable for flexible articles such as films. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2018046578 Brochure [Patent Document 2] U.S. Patent No. 5,767,230A Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, the challenge remains to provide more valuable polypropylene blends. [Means for solving the problem]
[0006] The present invention provides a mixed plastic polypropylene blend comprising: (i) 900 to less than 924 kg / m 3 Density determined according to DIN EN ISO 1183, (ii) soluble fraction (SF) content, determined according to CRYSTEX QC analysis, ranging from 3.0 to 12.0 wt.%; and (iii) the soluble fraction (SF) has an ethylene-propylene rubber (EPR) content of formula (2) of less than 7.0 wt. %, where the EPR corresponds to a fraction having a molar mass higher than 3.5 to 8 log M of the soluble fraction (SF) in TCB at 35°C, as determined by cross fractionation chromatography (CFC) analysis;
number
[0007] In particular, the present invention provides a mixed plastic polypropylene blend comprising: (i) 900 to less than 924 kg / m 3 Density determined according to DIN EN ISO 1183, (ii) soluble fraction (SF) content, determined according to CRYSTEX QC analysis, ranging from 3.0 to 12.0 wt.%; and (iii) the soluble fraction (SF) has an ethylene-propylene rubber (EPR) content of formula (2) of less than 7.0 wt.%, the EPR corresponding to a fraction having a molar mass higher than 3.5 to 8 log M of the soluble fraction (SF) in TCB at 35°C obtained by cross-fractionation chromatography (CFC) analysis;
number
[0008] The present invention also relates to the mixed plastic polypropylene blend in pellet form.The present invention further provides extruded articles made from the mixed plastic polypropylene blend and their use for packaging.
[0009] Surprisingly, it has been found that the mixed plastic polypropylene blends of the present invention provide improved flexibility that allows for application in many demanding end uses.
[0010] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. Although any methods and materials similar or equivalent to those described herein can be used in the practice for testing of the present invention, the preferred materials and methods are described herein. In describing and claiming the present invention, the following terminology will be used in accordance with the definitions set out below.
[0011] Unless expressly stated otherwise, use of the terms "a," "an," etc. refers to one or more.
[0012] As used herein, mixed plastics (also known as post-consumer waste) refers to objects that have completed at least their first use cycle (or life cycle), i.e., have already fulfilled their initial purpose, while industrial waste typically refers to manufacturing scrap that does not reach the consumer. According to the present invention, the waste stream is a post-consumer waste stream, and such waste streams may originate from conventional collection systems, such as those implemented in the European Union. Post-consumer waste materials may be characterized, for example, by a limonene content of 0.10 to 500 ppm (determined using solid-phase microextraction with standard addition (HS-SPME-GC-MS)). Mixed plastics may be defined, for example, by the presence of small amounts of compounds not typically found in virgin polypropylene blends, such as long-term degradation products of polystyrene, polyamide, polyester, wood, paper, limonene, aldehydes, ketones, fatty acids, metals, and / or stabilizers. Virgin polypropylene blends represent blends derived directly from the manufacturing process without intermediate use. Thus, virgin and recycled materials can be easily distinguished based on the absence or presence of contaminants such as limonene and / or fatty acids and / or paper and / or wood.
[0013] As a matter of definition, "mixed plastics" can be equated with detectable amounts of polystyrene and / or polyamide-6 and / or limonene and / or fatty acids. Mixed plastic polypropylene blends also have a broad molecular weight distribution because they are mechanical blends of numerous polypropylenes with some very small amounts of low density polyethylene and linear low density polyethylene. Those skilled in the art will appreciate that polypropylene from a variety of manufactures ends up in plastic waste streams, especially when pre-sorted into polyolefin-rich plastic waste streams.
[0014] Furthermore, it will be understood by those skilled in the art that the soluble fraction (SF) obtained by CRYSTEX QC analysis has an intrinsic viscosity (iV(SF)) in the range of 1.10 to less than 1.50 dL / g, typically found in materials from recycle streams. In a preferred embodiment of the present invention, the soluble fraction (SF) obtained by CRYSTEX QC analysis has an intrinsic viscosity (iV(SF)) in the range of 1.25 to less than 1.45 dL / g.
[0015] It is understood that the blended plastics may vary widely in composition, i.e., may include polyolefin homopolymers and polyolefin copolymers. Conventionally, the mixed plastic according to the present invention has been residual chalk content, determined as described below; residual talc content, determined as described below; Residual metal content (determined by x-ray fluorescence (XRF)), the remaining amount of paper, as determined below; the remaining amount of wood, as determined below; Total free fatty acid content measured by using headspace solid-phase microextraction (HS-SPME-GC-MS) ranging from 0.1 to 100 ppm may have one or more of:
[0016] Talc and Chalk Content: TGA following the steps below: Thermogravimetric analysis (TGA) experiments may be performed using a Perkin Elmer TGA8000. Approximately 10-20 mg of material is placed in a platinum pan. The temperature is equilibrated at 50°C for 10 minutes, then increased to 950°C under nitrogen at a heating rate of 20°C / min. The weight loss (WCO2) between approximately 550°C and 700°C is assigned to CO2 evolved from CaCO3, and therefore the chalk content is estimated as follows: Chalk content = 100 / 44 x WCO2 The temperature is then reduced to 300°C at a cooling rate of 20°C / min. The gas is then switched to oxygen and the temperature is increased again to 900°C. The weight loss in this process is assigned to carbon black (Wcb). Knowing the carbon black and chalk content, the ash content excluding chalk and carbon black is calculated as follows: Ash content=(ash residue)-56 / 44×WCO2-Wcb In the above formula, the ash residue is the weight percent measured at 900°C in the first step carried out under nitrogen. The ash content is assumed to be the same as the talc content of the investigated recycles.
[0017] Amount of paper and wood: Paper and wood are determined by conventional laboratory methods including grinding, flotation, microscopy and thermogravimetric analysis (TGA).
[0018] Limonene detected: Limonene quantification can be performed using solid-phase microextraction with standard addition (HS-SPME-GC-MS). 50 mg of ground sample was weighed into a 20 mL headspace vial, and after adding different concentrations of limonene and a glass-coated magnetic stir bar, the vial was closed with a silicone / PTFE-lined magnetic cap. Using a microcapillary (10 pL), known concentrations of diluted limonene standard were added to the sample. Additions of 0, 2, 20, and 100 mg were equivalent to 0, 0.1, 1, and 5 mg / kg of limonene. Additionally, standard amounts of 6.6, 11, and 16.5 mg / kg of limonene were used in conjunction with some of the samples tested in this study. Quantitation was performed using ion 93 acquired in SIM mode. Concentration of the volatile fraction was performed by headspace solid-phase microextraction using a 2 cm Stableflex 50 / 30 pm DVB / Carboxen / PDMS fiber at 60 °C for 20 min. Desorption is carried out directly in the heated injection port of the GCMS system at 270°C. GCMS parameters: Column: 30mHP 5 MS 0.25 x 0.25 Injector: Splitless, 0.75mm SPME liner, 270℃ Temperature program: -10℃ (1 min) Carrier gas: Helium 5.0, 31 cm / sec linear velocity, constant flow rate MS: Single quadrupole, direct interface, 280°C interface temperature Acquisition: SIM scan mode Scan parameters: 20~300amu SIM parameters: m / Z 93, dwell time 100 ms
[0019] Fatty Acid Detection: Fatty acids are quantified using headspace solid-phase microextraction with standard addition (HS-SPME-GC-MS). 50 mg of ground sample was weighed into a 20 mL headspace vial. After adding different concentrations of limonene and a glass-coated magnetic stir bar, the vial was closed with a silicone / PTFE-lined magnetic cap. Using a 10 μL microcapillary, known concentrations of diluted free fatty acid mixtures (acetic acid, propionic acid, butyric acid, pentanoic acid, hexanoic acid, and octanoic acid) were added to the sample at three different levels. Additions of 0 ng, 50 ng, 100 ng, and 500 ng were equivalent to 0 mg / kg, 1 mg / kg, 2 mg / kg, and 10 mg / kg of each individual acid. For quantification, ion 60 acquired in SIM mode was used for all acids except propanoic acid, in which case ion 74 was used. GCMS parameters: Column: 20mZB Wax plus 0.25 x 0.25 Injector: 5:1 split with glass-lined split liner, 250℃ Temperature program: 40°C (1 min), 6°C / min to 120°C, 15°C / min to 245°C (5 min) Carrier: Helium 5.0, 40 cm / sec linear velocity, constant flow rate MS: Single quadrupole, direct interface, 220°C interface temperature Acquisition: SIM scan mode Scan parameters: 46~250amu 6.6 scans / sec SIM parameters: m / z 60, 74, 6.6 scans / sec
[0020] For the purposes of the present invention, the mixed plastic polypropylene blend preferably comprises: a limonene content of 0.10 to 500 ppm, preferably 0.1 to 100 ppm, more preferably 0.1 to 50 ppm (determined using solid phase microextraction with standard addition (HS-SPME-GC-MS)), Polystyrene content up to 6.0% by weight, Talc content up to 3% by weight, Chalk content up to 1.0% by weight, Polyamide content up to 5.0% by weight, Fatty acid content of 1.0 to 100 ppm (determined using solid-phase microextraction with standard addition (HS-SPME-GC-MS)) The present invention has at least one of the following:
[0021] A blend refers to a mixture of two or more components, at least one of which is a polymer. Generally, a blend can be prepared by mixing two or more components. Suitable mixing procedures are known in the art.
[0022] Unless otherwise indicated, "%" refers to % by weight.
[0023] When referring to weight percentages of compositions and ingredients contained therein, it is understood that in accordance with the present invention, the total amount of ingredients does not exceed 100% (±1% rounding). DETAILED DESCRIPTION OF THE INVENTION
[0024] The mixed plastic polypropylene blend of the present invention comprises: (i) 900 to less than 924 kg / m 3 Density determined according to DIN EN ISO 1183, (ii) soluble fraction (SF) content, determined according to CRYSTEX QC analysis, ranging from 3.0 to 12.0 wt.%; and (iii) the soluble fraction (SF) has an ethylene-propylene rubber (EPR) content of formula (2) of less than 7.0 wt.%, the EPR corresponding to a fraction having a molar mass higher than 3.5 to 8 log M of the soluble fraction (SF) in TCB at 35°C obtained by cross-fractionation chromatography (CFC) analysis;
number
[0025] Preferably, the soluble fraction (SF) content, determined according to CRYSTEX QC analysis, is in the range of 4.0 to 11.0 wt.%, more preferably 5.0 to 10.0 wt.%, even more preferably 5.5 to 9.0 wt.%, especially 6.0 to 8.0 wt.%.
[0026] Preferably, the crystalline fraction (CF) content, determined according to CRYSTEX QC analysis, is in the range of 88.0 to 97.0 wt.%, more preferably 89.0 to 96.0 wt.%, even more preferably 90.0 to 95.0 wt.%, even more preferably 91.0 to 94.5 wt.%, and especially 92.0 to 94.0 wt.%.
[0027] Preferably, the mixed plastic polypropylene blend has ethylene units (C2) determined according to CRYSTEX QC analysis in the range of 2.0 to 9.0 wt%, more preferably 4.0 to 6.0 wt%, based on the total weight of the mixed plastic polypropylene blend. Without being bound by any theory, it is assumed that when the C2 units of a polyolefin material are determined according to CRYSTEX QC, the majority of the remaining polyolefin units can be attributed to propylene units (C3 units). Thus, the mixed plastic polypropylene blend preferably has propylene units (C3) determined according to CRYSTEX QC analysis in the range of 91.0 to 98.0 wt%, more preferably 94.0 to 96.0 wt%, based on the total weight of the mixed plastic polypropylene blend.
[0028] Preferably, the mixed plastic polypropylene blend has an ethylene content of the crystalline fraction (measured by infrared spectroscopy (IR) during CRYSTEX analysis) in the range of 1.0 to 15.0 wt%, more preferably 1.0 to 10.0 wt%, and even more preferably 2.0 to 6.0 wt%.
[0029] The mixed plastic polypropylene blend preferably has an ethylene content of the soluble fraction (measured by infrared spectroscopy (IR) during CRYSTEX analysis) in the range of 8.0 to 30.0 wt%, more preferably 10.0 to 25.0 wt%, and even more preferably 15.0 to 20.0 wt%.
[0030] Preferably, the soluble fraction (SF) has an ethylene-propylene rubber (EPR) content of formula (2) of 4.7 to less than 7.0 wt.%, more preferably 4.7 to 6.5 wt.%, even more preferably 5.0 to 6.2 wt.%, in particular 5.1 to 6.0 wt.%, wherein the EPR corresponds to a fraction having a molar mass higher than 3.5 to 8 log M of the soluble fraction (SF) in TCB at 35°C obtained by cross-fractionation chromatography (CFC) analysis,
number
[0031] Preferably, the soluble fraction (SF), determined according to CRYSTEX QC analysis, has an intrinsic viscosity (iV(SF)) in the range of 1.20 to 1.45 dl / g, more preferably 1.25 to 1.45 dl / g, even more preferably 1.25 to 1.40 dl / g, especially 1.25 to 1.35 dl / g.
[0032] Preferably, the mixed plastic polypropylene blend has a ratio of the molecular weight of the low crystalline polyethylene fraction (LCF-PE) (Mw LCF(60-85)) observed in a CFC analysis in the range of 60-85°C to the molecular weight of the crystalline ethylene-propylene copolymer (Mw EP Copo(103-109)) observed in a CFC analysis in the range of 103-109°C of 0.7 to less than 1.4, more preferably 0.8 to 1.3, even more preferably 0.9 to 1.2, especially 1.0 to 1.2.
[0033] Preferably, the mixed plastic polypropylene blend has a molecular weight of the low crystalline polyethylene fraction (LCF-PE) (Mw LCF(60-85)) observed in a CFC analysis in the range of 60-85°C in the range of 60,000 to 110,000 g / mol, more preferably 80,000 to 105,000 g / mol, especially 85,000 to 100,000 g / mol.
[0034] Preferably, the mixed plastic polypropylene blend has a low crystalline polyethylene fraction (LCF-PE) content of formula (5) of less than 7.0 wt%, more preferably less than 6.0 wt%, in particular less than 5.5 wt%, wherein the LCF-PE content is obtained by CFC analysis:
number
number
[0035] Preferably, the mixed plastic polypropylene blend has a Large Amplitude Oscillatory Shear - Non-Linear Factor (LAOS-NLF) (190 ° C, 1000%) of greater than 1.5, more preferably greater than 1.5 to 3.0, even more preferably greater than 1.5 to 2.5, especially greater than 1.5 to 2.3;
number
[0036] Preferably, the mixed plastic polypropylene blend comprises: L of 30.0 to 90.0, preferably 35.0 to 71.0 * , -5.0~0.0 a * , b between 0.0 and 15.0 * CIELAB color space (L * a * b * )
[0037] Preferably, the mixed plastic polypropylene blend has a melt flow rate (ISO 1133, 2.16 kg; 230°C) of 1.0 to 100.0 g / 10 min, preferably 2.0 to 20.0 g / 10 min, more preferably 2.0 to 11.0 g / 10 min, and most preferably greater than 2.0 to 10.0 g / 10 min. In another preferred embodiment, the mixed plastic polypropylene blend has a melt flow rate (ISO 1133, 2.16 kg; 230°C) of 2.0 to 50.0 g / 10 min, preferably 4.0 to 30.0 g / 10 min, more preferably 5.0 to 20.0 g / 10 min, especially 5.0 to 11.0 g / 10 min.
[0038] The mixed plastic polypropylene blend is a recycled material.
[0039] Preferably, the mixed plastic polypropylene blend comprises the following materials: a) Polystyrene b) Polyamide-6 c) Limonene determined using solid phase microextraction (HS-SPME-GC-MS) d) Fatty acids determined using solid phase microextraction (HS-SPME-GC-MS) It contains one or more of the following:
[0040] Preferably, the mixed plastic polypropylene blend contains up to 2.0 wt. %, more preferably in the range of 0.1 to 1.0 wt. %, of 3300 cm based on the total weight of the mixed plastic polypropylene blend. -1 Preferably, the mixed plastic polypropylene blend contains up to 2.0 wt. %, more preferably up to 1.0 wt. %, of a polyamide (PA6) as determined by FTIR spectroscopy using the absorption of the band at 1601 cm based on the total weight of the mixed plastic polypropylene blend. -1 The absorption of the bands of polystyrene (PS) was determined by FTIR spectroscopy.
[0041] Preferably, the mixed plastic polypropylene blend comprises up to 2.0 wt.%, more preferably in the range of 0.1 to 1.0 wt.%, chalk as determined by TGA based on the total weight of the mixed plastic polypropylene blend. Preferably, the mixed plastic polypropylene blend comprises up to 2.0 wt.%, more preferably in the range of 0.1 to 1.0 wt.%, talc as determined by TGA based on the total weight of the mixed plastic polypropylene blend. Preferably, the mixed plastic polypropylene blend comprises up to 2.0 wt.%, more preferably in the range of 0.1 to 1.0 wt.%, ash as determined by TGA based on the total weight of the mixed plastic polypropylene blend.
[0042] Preferably, the mixed plastic polypropylene blend contains up to 2 ppm, preferably up to 1 ppm, and in particular 0 ppm, of heavy metals selected from the group consisting of cadmium, chromium, mercury, lead, and mixtures thereof, as determined by XRF. In this regard, 0 ppm is understood to indicate that the detection limit has been reached. Preferably, the mixed plastic polypropylene blend contains up to 3000 ppm, preferably 100-2900 ppm, and in particular 1000-2600 ppm, of titanium, as determined by XRF.
[0043] Preferably, the density of the mixed plastic polypropylene blend, determined according to DIN EN ISO 1183, is between 900 and 923 kg / m 3 , more preferably 905 to 922, and even more preferably 910 to 921 mg / m 3 , especially 915-920 kg / m 3 is.
[0044] Preferably, the mixed plastic polypropylene blend has a η(Eta)(0.05 rad / s) at 200°C of 2000 to 4300 Pa.s, more preferably 2500 to 4000 Pa.s, especially 3000 to 4000 Pa.s.
[0045] Preferably, the mixed plastic polypropylene blend has a η(300 rad / s) at 200°C of 200 to 280 Pa.s, preferably 210 to 275 Pa.s, especially 240 to 270 Pa.s. Preferably, the mixed plastic polypropylene blend has a main peak heat of fusion as determined by DSC of 98 to 105 J / g, more preferably 99 to 104 J / g.
[0046] Preferably, the mixed plastic polypropylene blend has a tensile break strain determined according to ISO 527-2 / A, >96h of 100-250%, more preferably 120-230%, especially 130-200%. Preferably, the mixed plastic polypropylene blend has a tensile break strain determined according to ISO 527-2 / 2A, >24h of 140-235%, more preferably 160-230%, especially 180-225%.
[0047] Preferably, the mixed plastic polypropylene blend has a Shear Thinning Factor (STF), η(0.05) / η(300), of 9.5 to 16.0, preferably 10.0 to 14.5.
[0048] Preferably, the mixed plastic polypropylene blend is in the form of pellets. The process for providing the mixed plastic polypropylene blend of the present invention is very demanding. a) providing a precursor mixed plastics recycle stream (A); b) sieving the precursor mixed plastic recycle stream (A) to create a sieved mixed plastic recycle stream (B) having only articles with a longest dimension in the range of 30 to 400 mm; c) sorting the sieved mixed plastic recycle stream (B) with one or more optical sorters to produce a single-color sorted polyolefin recycle stream (C), wherein the sieved mixed plastic recycle stream (B) is sorted at least by color, and optionally by polyolefin type and / or article form; d) shredding the monochromatically separated polyolefin recycle stream (C) to form a flake polyolefin recycle stream (D); e) washing the flake polyolefin recycle stream (D) with a first alkaline aqueous wash solution (W1) having a pH in the range of 8.0 to 14.0, preferably 10.0 to 14.0, particularly 12.0 to 14.0, without the input of thermal energy, to produce a first suspended polyolefin recycle stream (E); f) removing said first alkaline aqueous wash liquid (W1) from said first suspended polyolefin recycle stream (E) to obtain a first washed polyolefin recycle stream (F); g) washing the first washed polyolefin recycle stream (F) with a second alkaline aqueous wash solution (W2) having a pH in the range of 12.0 to 14.0 to produce a second suspended polyolefin recycle stream (G), wherein sufficient heat energy is input into the system during washing to raise the temperature to a temperature in the range of 65 to 95°C; h) removing said second alkaline aqueous wash liquid (W2) and any material not floating on the surface of said second alkaline aqueous wash liquid from said second suspended polyolefin recycle stream (G) to obtain a second washed polyolefin recycle stream (H); i) drying the second washed polyolefin recycle stream (H) to obtain a dried polyolefin recycle stream (I); j) optionally separating the dried polyolefin recycle stream (I) into a light fraction and a heavy fraction polyolefin recycle stream (J); k) further sorting the heavy fraction polyolefin recycle stream (J) or the dried polyolefin recycle stream (I) in the absence of step j) through one or more optical sorters to remove any flakes containing materials other than the target polyolefin to obtain intermediate (K); l1) a quality control step in which the intermediate (K) from step k) is subjected to cross-fractionation chromatography (CFC) to determine the ethylene-propylene rubber (EPR) content of the soluble fraction (SF) and double-check whether said content is in the range of 0-12% by weight; m1) discarding intermediate (K) that does not have an EPR content of less than 7.0% by weight; n) optionally melt extruding and preferably pelletizing the intermediate (K) that has passed the quality control steps l1) / m1) to form the extruded, preferably pelletized recycled polypropylene blend (N) according to the invention, wherein preferably additives (Ad) are added in the molten state; o) optionally aerating the recycled polypropylene blend (N) or, in the absence of step n), the intermediate (K) that has passed through quality control step l1) / m1) to remove volatile organic compounds, thereby producing an aerated recycled polyolefin product (O), which is either an aerated extruded, preferably pelletized, recycled polypropylene product (O1) or an aerated recycled polyolefin flake (O2); wherein the intermediate (K) that has passed through the quality control steps l1) / m1) is first aerated to form said aerated recycled polypropylene flakes (O2) and then extruded, preferably by switching the order of steps n) and O) so that the additive (Ad) is added in the molten state to form an extruded, preferably pelletized, aerated recycled polypropylene product (O3).
[0049] It should be understood that the above process according to the present invention relates to providing a recycled polypropylene blend.
[0050] Preferably, the above-mentioned mechanical recycling process for polyolefins comprises: l2) a quality control step in which the intermediate (K) that has passed through the quality control step l1) / m1) is subjected to cross-fractionation chromatography (CFC) to determine the ratio of the molecular weight of the low crystalline polyethylene fraction (LCF-PE) (Mw LCF(60-85)) observed in the CFC analysis in the range of 60-85°C to the molecular weight of the crystalline ethylene-propylene copolymer (Mw EP Copo(103-109)) observed in the CFC analysis in the range of 103-109°C, and double-check whether the ratio is within the range of 0-2.5; m2) A step of discarding intermediate (K) that has passed through the quality control step l1) / m1) and does not have a (Mw LCF(60-85)) / (Mw EP Copo(103-109)) ratio in the range of 0.7 to less than 1.4; Further includes:
[0051] Preferably, the above-mentioned mechanical recycling process for polyolefins comprises: l3) a quality control step in which the intermediate (K) that has passed through quality control steps l1) / m1) and optionally quality control steps l2) / m2) is subjected to cross-fractionation chromatography (CFC) to determine the low crystalline polyethylene (LCF-PE) content and double-check whether said content is in the range of 0 to 12% by weight; m3) discarding the intermediate (K) that has passed the quality control steps l1) / m1) and optionally l2) / m2) and does not have an LCF-PE content of less than 7.0% by weight, preferably less than 6.0% by weight, In this regard, the LCF-PE content may be determined by CFC analysis,
number
[0052] In a particular embodiment, the above-mentioned mechanical recycling process of polyolefins comprises steps l2) / m2) and l3 / m3).
[0053] Preferably, the shredding in step d) of the above mechanical recycling process for polyolefins is a wet shredding process, in which the sorted polyolefin recycle stream (C) is first contacted with an aqueous alkaline solution (W0) having a pH in the range of 12.0 to 14.0, and the resulting suspension is subjected to shredding.
[0054] Preferably, the first aqueous cleaning liquid (W1) contains the detergent in an amount ranging from 0.1% to 1.0% by weight relative to the total weight of the first aqueous cleaning liquid (W1).
[0055] The detergent may be a commercially available detergent mixture or may be composed in any manner known to those skilled in the art. Suitable detergents include TUBIWASH SKP, TUBIWASH GFN, TUBIWASH EYE, and TUBIWASH TOP available from CHT, KRONES colclean AD 1004, KRONES colclean AD 1002, and KRONES colclean AD 1008 available from KIC KRONES, and P3-stabilon WT and P3 stabilon AL available from ECOLAB Ltd.
[0056] Preferably, the second alkaline aqueous wash liquid (W2) of the above-mentioned polyolefin mechanical recycling process is an alkaline aqueous solution of a base selected from the group consisting of calcium hydroxide, potassium hydroxide, magnesium hydroxide, sodium bicarbonate, sodium hydroxide and mixtures thereof, preferably sodium hydroxide. In this regard, the amount of base in the alkaline aqueous solution is preferably in the range of 0.05 to 10 wt %, more preferably in the range of 0.10 to 7.0 wt %, and most preferably in the range of 0.50 to 5.0 wt %, based on the total weight of the alkaline aqueous solution.
[0057] Preferably, the second aqueous cleaning liquid (W2) contains the detergent in an amount ranging from 0.1% to 1.0% by weight relative to the total weight of the second aqueous cleaning liquid (W2).
[0058] The detergent may be a commercially available detergent mixture or may be composed in any manner known to those skilled in the art. Suitable detergents include TUBIWASH SKP, TUBIWASH GFN, TUBIWASH EYE, and TUBIWASH TOP available from CHT, KRONES colclean AD 1004, KRONES colclean AD 1002, and KRONES colclean AD 1008 available from KIC KRONES, and P3-stabilon WT and P3 stabilon AL available from ECOLAB Ltd.
[0059] Preferably, the alkaline aqueous wash liquid removed in step h) of the above polyolefin mechanical recycling process is recycled for use as the first alkaline aqueous wash liquid (W1) and, if present, as the alkaline aqueous wash liquid (W0).
[0060] Preferably, the precursor mixed plastic recycle stream (A) of the above polyolefin mechanical recycling process is derived from post-consumer waste, post-industrial waste, or a combination thereof, preferably from post-consumer waste.
[0061] Preferably, the precursor mixed plastic recycle stream (A) of the above-mentioned polyolefin mechanical recycling process is derived from post-consumer waste, which constitutes more than 80 wt.%, preferably more than 90 wt.%, based on the total weight of the flexible polypropylene post-consumer waste. The flexible polypropylene post-consumer waste may be derived from films, bags, pouches, etc.
[0062] Those skilled in the art will recognize multiple ways to achieve the sieving in step b), and therefore, this sieving step is not particularly limited. However, preferably, the sieving in step b) is achieved by using a sieve with a sieve diameter of 30 mm and a sieve with a sieve diameter of 400 mm to divide the precursor mixed recycle stream into three streams: a small item stream with a longest dimension of less than 30 mm, an oversized item stream with a longest dimension of more than 400 mm, and a sieved mixed plastic recycle stream (B). The small item stream and the oversized item stream may be discarded or transferred for use in other polyolefin mechanical recycling processes.
[0063] In the broadest sense, any optical sorter can be used to achieve the sorting of step c) (and step k)). In the context of the present invention, the term "optical sorter" refers to a sorting unit that uses any form of electromagnetic radiation (visible or invisible) to distinguish pieces of the sieved mixed plastic recycling stream (B).
[0064] Suitable methods for sorting recycling streams by color include camera systems (operating in the visible range of the electromagnetic spectrum) and visible reflectance spectroscopy.
[0065] Suitable methods for sorting recycle streams by polyolefin type include near-infrared spectroscopy, mid-infrared spectroscopy, high-speed laser spectroscopy, Raman spectroscopy, and Fourier transform infrared (FTIR) spectroscopy, with near-infrared spectroscopy being particularly preferred.
[0066] Suitable methods for sorting recycling streams by type of item include camera systems (operating in the visible range of the electromagnetic spectrum).
[0067] Preferably, the sorting in step c) is done by color and polyolefin type, which means that the mono-color sorted polyolefin recycle stream (C) is mono-colored and all articles contain a single polyolefin.
[0068] In some embodiments, a single sensor type (e.g., a near-infrared sensor or a camera system operating in the visible range of the electromagnetic spectrum) can be used to distinguish between multiple characteristics (e.g., color and polyolefin type, or color and article morphology). Additionally, many near-infrared sensor units may include a visible reflectance unit or be configured to measure both the near-infrared and visible regions of the electromagnetic spectrum, meaning that a single sensor unit may use multiple detection methods.
[0069] The term "article form" as used herein refers to the shape and form of the articles present in the polyolefin recycling stream. Such articles may be in the form of films, bags, and pouches, among others, which are considered flexible articles, or in the form of molded articles such as food containers and trays, skin care product containers, plastic bottles, among others, which are considered rigid articles. Commercially available optical sorters, such as Tomra Autosort, RTT Steinert Unisort, Redwave, and Pellenc, can separate so-called rigid articles from so-called flexible articles by utilizing aerodynamic properties (i.e., a gas stream is usually applied to the stream, and rigid articles fall in a different arc than flexible articles), and can convert the stream containing such articles into so-called rigid and flexible streams.
[0070] To achieve the sorting in step c), multiple detection methods and / or multiple sensors can be used.
[0071] More preferably, the sorting in step c) is carried out by color, type of polyolefin, and type of article, which means that the monochromatically sorted polyolefin recycle stream (C) is monochromatic, all articles contain a single polyolefin, and the stream contains only rigid or flexible articles.
[0072] While the above process is suitable for isolating any desired polyolefin from a mixed polyolefin recycle stream, isolation of polyethylene or polypropylene is particularly desirable because these are likely to be the major polyolefin components of any mixed polyolefin recycle stream, and the isolated polyethylene or isolated polypropylene can be fed into a pure recycled polyolefin stream or extruded and pelletized to obtain pellets of the desired polyolefin, i.e., polyethylene or polypropylene. Preferably, the monochromatically separated polyolefin recycle stream (C) of the above polyolefin mechanical recycling process is a monochromatically separated polypropylene recycle stream.
[0073] The sorting in step c) can be achieved through a simple sorting algorithm where the optical sensor is programmed to evaluate which pieces should be selected or rejected based on a simple binary decision, or more complex AI-based systems can be used to achieve more accurate sorting, especially when sorting by item morphology.
[0074] Step k) uses at least a first optical sorter to remove any flakes containing materials other than the target polyolefin, the selection criteria for this optical sorter being that if any material other than the target polyolefin is present in a given flake, this flake will be separated from the stream, resulting in a purified polyolefin recycle stream.
[0075] Multiple optical sorters with the same sorting criteria may be arranged in series to improve the purity of intermediate (K). Alternatively or additionally, multiple optical sorters may be arranged in series to sort according to different criteria, such as color and / or article morphology, but preferably each of the one or more optical sorters of step k) sorts by polyolefin type as described above.
[0076] Step h) involves removing the second alkaline aqueous wash liquid (W2) and any material that does not float on the surface of the second aqueous wash liquid from the second suspended polyolefin recycle stream (G) to obtain a second washed polyolefin recycle stream (H).
[0077] In contrast to step f), in which only small amounts of foreign matter suspended or dissolved in the alkaline aqueous cleaning solution are removed, step h) involves a so-called sink-float separation, whereby any and all material that does not float to the surface of the alkaline aqueous cleaning solution is removed. Those skilled in the art will recognize that this is equivalent to a concentration of 1.00 g / cm 3 It will be appreciated that this is effective in removing any foreign matter having a density greater than 1.
[0078] Step k) may be carried out in a flake sorter, preferably a belt flake sorter.
[0079] The mixed plastic polypropylene blends outlined above can be used to make any suitable article.
[0080] In a further aspect, the present invention relates to extruded articles made from the mixed plastic polypropylene blends outlined above.
[0081] Those skilled in the art will know how to obtain extruded articles under standard conditions.
[0082] Preferably, the extruded article is a film.
[0083] Preferably, the film is extruded at a melt temperature of 200 to 260°C, preferably 210 to 250°C, especially 220 to 245°C.
[0084] Preferably, the film is extruded at a screw speed in the range of 40 to 500 rpm, preferably 50 to 400 rpm, especially 60 to 300 rpm.
[0085] Preferably, the film is extruded using a chill roll, preferably with a chill roll temperature in the range of 15 to 80° C. Those skilled in the art will know the specific chill roll temperature to select for a particular material. Preferably, the film has a thickness of 10 to 150 μm, more preferably 20 to 120 μm, even more preferably 30 to 100 μm, especially 35 to 80 μm.
[0086] Preferably, the film has an impact failure weight, determined by the free falling dart test according to ASTM D1709, of 40 to 90 g, more preferably 45 to 80 g, especially 50 to 70 g.
[0087] Preferably, the film has a normalized total penetration energy of film puncture, determined according to ISO 7765-2, 4.4 m / s, 23°C, of more than 2.2 J / mm, more preferably from 2.2 to 5.0 J / mm, especially from 2.3 to 4.0 J / mm.
[0088] Preferably, the film has an MD relative tear resistance, determined according to ISO 6383-2, of less than 12.5 N / mm, more preferably 4.0 to 11.0 N / mm, especially 5.0 to 10.5 J / mm. Preferably, the film has a TD relative tear resistance, determined according to ISO 6383-2, of less than 75.0 J / mm, more preferably 40.0 to less than 75.0 J / mm, especially 50 to 72.0 J / mm.
[0089] Preferably, the film has an MD tensile modulus, determined according to ISO 527-3, 23°C, of greater than 430 MPa, more preferably 435 to 800 MPa, especially 470 to 630 MPa. Preferably, the film has a TD tensile modulus, determined according to ISO 527-3, 23°C, of greater than 415 MPa, more preferably 420 to 750 MPa, especially 450 to 600 MPa.
[0090] Preferably, the film has an MD (longitudinal, machine direction) gloss, film exterior, determined according to ASTM D2457, 45°, of greater than 20°, more preferably 21 to 40°, especially 22 to 30°. Preferably, the film has a TD (transverse direction) gloss, film exterior, determined according to ASTM D2457, 45°, of greater than 17°, more preferably 19 to 35°, especially 20 to 28°.
[0091] Preferably, the film has a transparency, determined according to ASTM D1003, of greater than 33%, more preferably 35 to 80%, especially 45 to 75%. Preferably, the film has a haze, determined according to ASTM D1003, of less than 75%, more preferably 35 to 72%, especially 50 to 65%. Preferably, the film has a diffuse luminous transmittance, determined according to ASTM D1003, of less than 46.5%, more preferably 20 to less than 46.5%.
[0092] In a further aspect, the present invention relates to the use of the mixed plastic polypropylene blends outlined above for packaging.
[0093] All the above preferred aspects, definitions and embodiments also apply to the use of the above outlined mixed plastic polypropylene blends for extruded articles and packaging.
[0094] The gist of the present invention is further outlined in the following examples. [Example]
[0095] Experimental Department The following examples are included to demonstrate certain aspects and embodiments of the claimed invention. However, it should be understood by those of ordinary skill in the art that the following descriptions are illustrative only and should not be construed as limiting the invention in any way.
[0096] 1. Test Method a) Melt flow rate Melt flow rate was measured at 230°C under a 2.16 kg load (MFR2) as indicated. Melt flow rate is the amount of polymer in grams that an ISO 1133 standardized testing apparatus will extrude under a 2.16 kg load at a temperature of 230°C in 10 minutes. MFR2 (230°C) is measured in accordance with ISO1133 (230°C, 2.16 kg load).
[0097] b) Tensile modulus [MPa] Tensile modulus was measured according to ISO 527-2 (crosshead speed = 50 mm / min; 23 °C unless otherwise stated) using injection-molded specimens (dogbone shape, 4 mm thick) as described in EN ISO 1873-2. A speed of 50 mm / min was used to determine the yield stress.
[0098] c) Notched Charpy impact strength (NIS) The notched Charpy impact strength was determined according to ISO 179-1 / 1eA on notched 80 mm x 10 mm x 4 mm specimens (specimens prepared according to ISO 179-1 / 1eA). The test temperatures were 23 ± 2 °C and -20 °C. Injection molding was performed according to ISO 19069-2.
[0099] d) Flexural modulus [MPa] The flexural modulus was determined according to ISO 178 Method A (three-point bending test) on 80 mm x 10 mm x 4 mm specimens. According to the standard, a test speed of 2 mm / min and a support distance of 16 times the thickness were used. The test temperature was 23 ± 2 °C. Injection molding was performed according to ISO 19069-2.
[0100] e) DSC analysis, melting temperature (Tm) and heat of fusion (ΔHf), crystallization temperature (Tc), heat of crystallization (ΔHc) and heat of fusion (ΔHm) DSC was measured on 5-7 mg samples using a TA Instrument Q2000 differential scanning calorimetry (DSC). DSC was performed in accordance with ISO 11357 / Part 3 / Method C2, with a heat / cool / heat cycle at a scan rate of 10 °C / min over the temperature range of -30 to +225 °C. The crystallization temperature (Tc) was determined from the cooling step, and the melting temperature (Tm) and enthalpy of fusion (ΔHm) can be determined from the second heating step. The degree of crystallinity can be calculated from the enthalpy of fusion by assuming a ΔHm value of 209 J / g for fully crystalline polypropylene (see Brandrup, J., Immergut, E.H., eds., Polymer Handbook, 3rd ed., Wiley, New York, 1989; Chapter 3).
[0101] f) Crystalline and soluble fractions and their respective characteristics (Crystex analysis) The crystalline fraction (CF) and soluble fraction (SF) of the polyolefin (PO) compositions, the final ethylene unit content of the PO compositions, the ethylene unit content of each fraction, and the intrinsic viscosity of each fraction were analyzed by a CRYSTEX QC Polymer Char (Valencia, Spain) according to ISO 6427 Annex B:1992(E). A schematic diagram of the CRYSTEX QC instrument is presented in Del Hierro, P.; Ortin, A.; Monrabal, B.; "Soluble Fraction Analysis in Polypropylene," The Column, February 2014, pp. 18-23. Crystalline and amorphous fractions are separated by temperature cycling: dissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160°C, crystallization at 40°C, and redissolution in 1,2,4-TCB at 160°C. Quantification of SF and CF and determination of ethylene content (C2) are achieved by an infrared detector (IR4), and an online two-capillary viscometer is used for determination of intrinsic viscosity (IV). The IR4 detector detects two distinct bands (CH stretching vibration (approximately 2960 cm)) that can be used to determine the concentration and ethylene content in ethylene-propylene copolymers (EP copolymers). -1 (mainly) and CH x Stretching vibration (2700~3000cm -1 )) is a multi-wavelength detector that detects IR absorbance at 2 wt% to 69 wt% ethylene content ( 13 A series of eight EP copolymers with different ethylene content (determined by C-NMR) were used to calibrate, each at various concentrations ranging from 2 to 13 mg / ml. To simultaneously consider both characteristics, concentration and ethylene content, for the various polymer concentrations expected during Crystex analysis, the following calibration equation was applied: Formula 1: Conc = a + b × Abs(CH) + c × (Abs(CH x )) 2 +d×Abs(CH3)+e×(Abs(CH3) 2 +f×Abs(CH x )×Abs(CH3) Formula 2: CH3 / 1000C=a+b×Abs(CH x )+c×Abs(CH3)+d×(Abs(CH3) / Abs(CH x ))+e×(Abs(CH3) / Abs(CH x )) 2 The constants a to e in Equation 1 and the constants a to f in Equation 2 were determined using least squares regression analysis. Formula 3: CH3 / 1000C is converted to ethylene content (wt%) using the following relationship: Wt% (ethylene in EP copolymer) = 100-CH3 / 1000TC x 0.3 The amounts of soluble fraction (SF) and crystalline fraction (CF) are correlated by XS calibration with the "cold xylene soluble" (XCS) and "cold xylene insoluble" (XCI) fractions, respectively, determined according to standard gravimetric methods according to ISO 16152. XS calibration is achieved by testing various EP copolymers with cold xylene soluble (XCS) contents ranging from 2 to 31 wt%. The determined XS calibration is linear (Equation 4). Weight%XCS=1.01×Weight%SF The intrinsic viscosities (IV) of the parent EP copolymer and its soluble fraction (SF) and crystalline fraction (CF) are determined using an online two-capillary viscometer and correlated with the corresponding IV determined by standard methods in decalin according to ISO 1628-3. Calibration is achieved using several commercially available EPPP copolymers with IV = 2-4 dL / g. The determined calibration curve between Vsp and IV, measured in a CRYSTEX QC and normalized by concentration (c), is linear (Equation 5). IV(dl / g)=a×Vsp / c It has a slope of a=16.2. A sample of the PO composition to be analyzed is weighed at a concentration of 10 mg / ml to 20 mg / ml. After automatic filling of the vial with 1,2,4-TCB containing 250 mg / l 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample is dissolved at 160°C with constant stirring at 400 rpm to 800 rpm until complete dissolution is achieved, typically for 60 minutes. To avoid sample degradation, the polymer solution is covered with a N2 atmosphere during dissolution. A defined volume of sample solution is injected into a column packed with an inert carrier, where the sample is crystallized and the soluble fraction is separated from the crystalline portion. This process is repeated twice. During the first injection, the entire sample is measured at high temperature to determine the IV [dl / g] and C2 [wt%] of the PO composition. During the second injection, the soluble fraction (SF, at low temperature, 40°C) and the crystalline fraction (CF, at high temperature, 160°C) are determined in the crystallization cycle (wt% SF, wt% C2, IV).
[0102] of C2 content for calibration standards13 Determination based on C NMR spectroscopy quantitative 13 C{ 1 The {H} NMR spectrum 1 H and 13 All spectra were recorded in solution using a Bruker Avance III 400 NMR spectrometer operating at 400.15 and 100.62 MHz for C, respectively. 13 All air pressures were recorded using nitrogen gas, using a 10 mm extended temperature probe head optimized for 1000 Hz. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) with chromium(III) acetylacetonate (Cr(acac)3), providing a 65 mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, after initial sample preparation in a heat block, the NMR tube was further heated in a rotary oven for at least 1 h. After insertion into the magnet, the tube was spun at 10 Hz. This setup was chosen primarily due to the high resolution and quantitative nature required for accurate ethylene content determination. Standard single-pulse excitation without NOE was employed using an optimized tip angle, a 1 s recycle delay, and a bilevel WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D., Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired per spectrum. Quantitative 13 C{ 1The {H} NMR spectra were processed and integrated, and relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the solvent chemical shift. This approach allowed for comparable referencing even in the absence of this structural unit. Characteristic signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950), and the comonomer fraction was calculated as the fraction of ethylene in the polymer relative to all monomers in the polymer. fE=(E / (P+E) The comonomer fraction is 13 C{ 1 Quantification was performed using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) by integration of multiple signals over the entire spectral region of the {H} spectrum. This method was chosen for its robustness and ability to account for the presence of positional defects, if necessary. The integration region was slightly adjusted to increase applicability over the entire range of comonomer contents encountered. For systems with very low ethylene content, where only isolated ethylene in the PPEPP sequence is observed, the method of Wang et al. was modified to reduce the impact of integration of sites that are no longer present. This approach reduces overestimation of ethylene content for such systems, which in turn reduces the number of sites used to determine absolute ethylene content. E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ)) This was achieved by reducing it to Using this set of sites, the corresponding integral equation can be written, using the same notation as used in Wang et al.'s paper (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157): E=0.5(I H +I G +0.5(I C +I D )) The equation used for absolute propylene content was not modified. Comonomer incorporation in mole percent was calculated from the mole fraction. E [mol%] = 100 × fE Comonomer incorporation in weight percent was calculated from the mole fraction. E[weight%]=100×(fE×28.06) / ((fE×28.06)+((1-fE)×42.08)) g) Density Density is measured according to ISO 1183-187. Sample preparation is by compression molding according to ISO 1872-2:2007.
[0103] h) Cross-fractionation chromatography The chemical composition distribution, as well as the molecular weight distribution and the corresponding molecular weight averages (Mn, Mw and Mv) at specific elution temperatures (polymer crystallinity in solution) were determined by fully automated cross-fractionation chromatography (CFC) as described by Ortin A., Monrabal B., Sancho-Tello J., Macromol. Symp., 2007, 257, 13-28. Cross-fractionation chromatography (TREF × SEC) was performed using a CFC apparatus (PolymerChar, Valencia, Spain). Concentration was monitored using a 4-band IR5 infrared detector (PolymerChar, Valencia, Spain). The polymer was dissolved at a concentration of approximately 1 mg / ml at 160 °C for 150 min. The weighed sample was packed into a stainless steel mesh MW 0.077 / D 0.05 mm to avoid the injection of possible gels and polymers that are not soluble in TCB at 160° C., such as PET and PA. Once the sample was completely dissolved, a 0.5 ml aliquot was loaded onto a TREF column and stabilized for a while at 110°C. The polymer was crystallized and precipitated by applying a constant cooling rate of 0.1°C / min to a temperature of 30°C. A discontinuous elution process was performed using the following temperature steps: (35, 40, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 103, 106, 109, 112, 115, 117, 119, 121, 123, 125, 127, 130, 135, and 140). For the second dimension, GPC analysis, three PL Olexis columns and one Olexis Guard column (Agilent, Church Stretton, UK) were used as the stationary phase. The eluent was 1,2,4-trichlorobenzene (TCB, stabilized with 250 mg / L 2,6-di-tert-butyl-4-methyl-phenol) at 150 °C and a constant flow rate of 1 mL / min. The column set was calibrated using universal calibration (according to ISO 16014-2:2003) with at least 15 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11,500 kg / mol. PS molecular weights were converted to PP molecular weight equivalents using the following Mark Houwink constants: K PS =19×10 -3 mL / g, α PS =0.655 K PP =19×10 -3 mL / g, α PP =0.725
[0104] Calibration data was fitted using a third order polynomial fit. Data processing was performed using software provided by PolymerChar with the CFC instrument.
[0105] Calculation of the relative fraction of iso-PP in wt% at a specific molecular weight and elution temperature range In the first step, to calculate the relative fraction in wt% of iso-PP at a particular molecular weight and elution temperature region, it is necessary to calculate the amount of iso-PP in wt% from the CFC contour map. IsoPP (wt%) = 100 - EPR fraction - PE fraction Equation (1) In the above formula, EPR is the fraction with a molar mass higher than 3.5 log M of the soluble fraction (SF) in TCB at 35° C. obtained by CFC analysis.
number
number
[0106] The highly crystalline PE fraction (HCF-PE) is defined as the portion of the PE fraction that elutes at 90°C to 100°C.
number
number
[0107] Calculation of Mw LCF (60-85) and Mw EP Copo (103-109℃) The Mw LCF (60-85°C) and Mw EP Copo (103-109°C) are calculated using the following formula:
number
[0108] Basic References: Zhang, Macromol Symp.282(2009), 111-127. W. Yau, D. Gillespie, Polymer 42(2001) 8947-8958. Monrabal, Encyclopedia of Analytical Chemistry, edited by RAMeyers, John Wiley & Sons Ltd., 2000. Nakano, Y.Goto, J.Appl.Polym.Sci.(1981), 26, 4217. W. Yau, Macromol. Symp. 2007, 257, 29-45. Faldi, JBPSoares, Polymer 42(2001) 3057-3066. Ortin, B.Monrabal, J.Sancho-Tello, Macromol.Symp. 257(2007), 13-28. Li Pi Shan, D.Gillespie, L.Hazlitt, Ecorep 2005. Lyon.
[0109] i) Large amplitude oscillatory shear (LAOS) Nonlinear viscoelastic behavior under shear flow has been investigated using large-amplitude oscillatory shear. This method requires the application of a sinusoidal strain amplitude γ0 imposed at a given angular frequency ω for a given time t. If the applied sinusoidal strain is sufficiently high, a nonlinear response is generated. In this case, the stress σ is a function of the applied strain amplitude, time, and angular frequency. Under these conditions, the nonlinear stress response is still a periodic function; however, it can no longer be represented by a single harmonic sinusoid. The stress [0-0] resulting from the nonlinear viscoelastic response can be expressed by a Fourier series including harmonic contributions.
number
[0110] In the above formula, σ is the stress response, t is the time, ω is the frequency, γ0 is the strain amplitude, n is the harmonic number, G' n is the nth-order elastic Fourier coefficient, G” n is the nth-order viscous Fourier coefficient.
[0111] The nonlinear viscoelastic response was analyzed by applying large amplitude oscillatory shear (LAOS). Time sweep measurements were performed on an Alpha Technologies RPA2000 rheometer coupled with a standard biconical die. The test chamber was sealed and subjected to a pressure of approximately 6 MPa during the course of the measurement. LAOS testing was performed at a temperature of 190°C, an angular frequency of 0.628 rad / s, and a strain of 1000%. To ensure steady-state conditions were reached, the nonlinear response was determined only after at least 20 cycles per measurement were completed. The large amplitude oscillatory shear nonlinearity factor (LAOS_NLF) was calculated as:
number
[0112] [1] J.M. Dealy, K.W. Issbrun, Melt Rheology and Its Role in Plastics Processing: Theory and Applications, edited by Van Nostrand Reinhold, New York (1990) [2] S. Filipe, Non-Linear Rheology of Polymer Melts, AIP Conference Proceedings 1152, pp. 168-174 (2009) [3] M. Wilhelm, Macromol. Mat. Eng. 287, 83-105 (2002) [4] S. Filipe, K. Hofstadler, K. Klimke, ATTran, Non-Linear Rheological Parameters for Characterization of Molecular Structural Properties in Polyolefins, Proceedings of Annual European Rheology Conference, 135(2010) [5] S. Filipe, K. Klimke, A.T.Tran, J. Reussner, Proceedings of Novel Non-Linear Rheological Parameters for Molecular Structural Characterization of Polyolefins, Novel Trends in Rheology IV, Zlín, Czech Republic (2011) [6] K. Klimke, S. Filipe, ATTran, Non-linear rheological parameters for characterization of molecular structural properties in polyolefins, Proceedings of European Polymer Conference, Granada, Spain (2011)
[0113] j) Presence of polyamide-6 and polystyrene FTIR spectroscopy revealed a 1601 cm -1 (PS) and 3300 cm -1 The absorption of the band in (PA6) is used.
[0114] k) Odor VDA270-B3 VDA 270 is the determination of odor characteristics of trim materials in automobiles. In this study, odor is determined according to VDA 270 (2018) variant B3. The odor of each sample is evaluated by each evaluator according to the VDA 270 scale after lifting the jar lid as low as possible. The six-point scale consists of the following grades: Grade 1: not perceptible; Grade 2: perceptible but not unpleasant; Grade 3: clearly perceptible but not unpleasant; Grade 4: unpleasant; Grade 5: strongly unpleasant; and Grade 6: intolerable. Evaluators remain silent during the evaluation and are not allowed to bias each other by discussing their individual results during the test. Evaluators are also not allowed to adjust their evaluations after testing another sample. For statistical reasons (and as accepted by VDA 270), evaluators are forced to use the entire process in their evaluation. Therefore, the odor grade is based on the average of all individual evaluations, rounded to the nearest integer.
[0115] l) CIELAB color space (L * a * b * ) CIE L measured according to DIN EN ISO11664-4 * a * b * In the uniform color space, the color coordinates are: * -Brightness coordinate;a * - red / green coordinates, + a * indicates red, -a * indicates green;b * -yellow / blue coordinate, +b * indicates yellow, -b * indicates blue. * , a * , and b * The coordinate axes define the three-dimensional CIE color space. Standard Konica Minolta Colorimeter CM-3700A.
[0116] m) Amount of metal It was determined by x-ray fluorescence (XRF).
[0117] n) Inorganic residue TGA according to DIN ISO 1172:1996 using a Perkin Elmer TGA8000. Approximately 10-20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes, then increased to 950°C at a heating rate of 20°C / min under nitrogen. Ash content was assessed as wt% at 850°C.
[0118] o) Dynamic shear measurements (η(2.7kPa) and η(300rad / s)) Dynamic shear characterization of polymer melts follows ISO standards 6721-1 and 6721-10. Measurements were performed on an Anton Paar MCR501 stress-controlled rotational rheometer equipped with a 25 mm parallel plate geometry. Measurements were performed on compression-molded plates using a nitrogen atmosphere and strain settings within the linear viscoelastic region. Oscillatory shear tests were performed at 200 °C, applying a frequency range of 628 to 0.01 rad / s. Data evaluation was performed with 5 data points per decade, and logarithmic ramped strains of 2 to 7% were used. The plate-plate geometry has a diameter of 25 mm and uses a gap size of 1.3 mm. Trimming was performed at 1.4 mm. In dynamic shear experiments, the probe is subjected to uniform deformation with a sinusoidally varying shear strain or shear stress (strain and stress controlled modes, respectively). In controlled strain experiments, the probe is subjected to a sinusoidal strain that can be expressed as: γ(t)=γ0sin(ωt) (1) If the applied strain is within the linear viscoelastic region, the resulting sinusoidal stress response can be given by: σ(t)=σ0sin(ωt+δ) (2) In the above formula, σ0 and γ0 are the stress amplitude and strain amplitude, respectively; ω is the angular frequency, δ is the phase difference (loss angle between the applied strain and the stress response), t is time. Dynamic test results are typically expressed in terms of several different rheological functions: the shear storage modulus G', the shear loss modulus G", the complex shear modulus G* , complex shear viscosity η * , the dynamic shear viscosity η′, the heterophase component of the complex shear viscosity η″, and the loss tangent tan δ, and the rheological function can be expressed as:
number
[0119] η(xkPa) is determined according to Equation 9. η(xkPa)=(G * = x kPa) for η * [Pa.s] (9)
[0120] For example, η(2.7 kPa) is defined by the value of the complex viscosity determined for a value of the complex modulus equal to 2.7 kPa. η (xrad / s) is determined according to Equation 10. η(xrad / s)=η for (ω=xrad / s) * [Pa.s] (10) For example, η(300 rad / s) is determined by the value of the complex viscosity determined in a frequency sweep of 300 rad / s. Similarly, η(0.05 rad / s) is determined by the value of the complex viscosity determined with a frequency sweep of 0.05 rad / s.
[0121] p) Shear thinning factor (STF) is defined as follows:
number
[0122] References [1] "Rheological characterization of polyethylene fractions", Heino, E.L., Lehtinen, A., Tanner J., Seppala, J., Neste Oy, Porvoo, Finland, Theor. Appl. Rheol., Proc. Int. Congr. Rheol., 11th (1992), 1, 360-362 [2] "The influence of molecular structure on some rheological properties of polyethylene", Heino, EL, Borealis Polymers Oy, Porvoo, Finland, Annual Transactions of the Nordic Rheology Society, 1995. [3] Definition of terms relating to the non-ultimate mechanical properties of polymers, Pure & Appl. Chem., Vol. 70, No. 3, pp. 701-754, 1998.
[0123] q) Dynamic shear measurements for the determination of the crossover modulus Gc, the crossover frequency W(c), the polydispersity index (PI), and the zero shear viscosity η0 The PI is determined by so-called frequency sweep at 200 °C in a nitrogen atmosphere using a plate-plate arrangement with a diameter of 25 mm and a gap size of 1.3 mm. Trimming is performed at 1.4 mm. An angular frequency range of 628 to 0.01 rad / s is used, with data evaluation of 5 data points per decade and a logarithmic slope strain of 2 to 7%. Dynamic shear measurements determine the loss modulus G"(w) and storage modulus G'(w) as a function of angular frequency. The crossover frequency w c Crossover modulus G at (also written as W(c)) c is the intersection point of the functions G'(w) and G"(w). The polydispersity index is PI=100000 / G c (12) is defined as, Pa -1 It is shown as follows. The zero shear viscosity η is calculated via the RheoPlus Rheometer software (by Anton Paar GmbH) using the model of Carreau and Yasuda (method "Carreau Yasuda I model").
[0124] References: [1] Bafna, SS "Is the Cross-Over Modulus a Reliable Measure of Polymeric Polydispersity?" Journal of Applied Polymer Science, Vol. 63, pp. 111-113, 1997. [2] Steeman, P.A.M. "A numerical study of various rheological polydispersity measures," Rheologica Acta, Vol. 37(6), pp. 583-592, 1998 [3] Zeichner GR and Patel PD "A Comprehensive Evaluation of Polypropylene Melt Rheology", Conference Proceeding, Chemical engineering for world development, pp. 333-337, 1981
[0125] r) Screening of organic emissions by thermal desorption analysis, TD GC-FID This method describes the semi-quantitative determination of organic compounds released from polyolefins. It is similar to VDA 278 (October 2011) but includes certain adjustments. Immediately after production, the samples (injection-molded plaques, DIN-A5) are sealed in aluminum-coated polyethylene bags and delivered to the laboratory within 14 days. In the laboratory, they are stored open at temperatures below 25°C for 7 days. After this period, 60 ± 5 mg aliquots are prepared from the stored samples. Trimming of the aliquots should aim for maximum coherent area. Creating the largest possible surface area by cutting the aliquot into smaller pieces is not the goal. The diameter of the sample injection tube should be used initially. Its length and thickness should be chosen appropriately, taking into account the specific aliquot weight. The aliquots are directly desorbed using heat and a stream of helium gas. Volatile and semivolatile organic compounds are extracted into the gas stream and cryo-focused before injection into a gas chromatography (GC) system for analysis. The method involves two extraction stages. For low boiling substances (LBS) analysis, an aliquot is desorbed at 90°C for 30 minutes to determine volatile organic compounds in the boiling / elution range up to n-C25 (n-pentacosane). For high boiling substances (HBS) analysis, an additional desorption step of the same aliquot is performed at 120°C for 60 minutes to determine semivolatile compounds in the boiling / elution range from n-C14 (n-tetradecane) to n-C32 (n-dotriacontane). Similar to the VOC and FOG values in VDA278, semi-quantitative and respective calibrations are applied, with LBS calculated as toluene equivalents (TE) and HBS calculated as hexadecane equivalents (HE). Results are expressed in μg / g. The integration parameters for LBS and HBS evaluation are selected so that the "area rejection" corresponds to an area of 1 μg / g (TE and HE, respectively). Therefore, smaller peaks are not added to the semiquantitative results. The GC oven program is kept the same regardless of whether a calibration run, LBS run, or HBS run is performed. The program starts at 50 °C (hold for 1 min), followed by a heating rate of 10 °C / min and an end temperature of 320 °C (hold for 10 min). For the GC column, an Agilent DB5: 50 m x 250 μm x 0.25 μm (or equivalent) is used. This method requires a GC system with a temperature-programmed desorption system TDS3 (Gerstel) and a cooled injection system CIS4 (Gerstel), as well as a flame ionization detector (FID), but does not require a mass spectrometer. The CIS end temperature is always set to 380 °C instead of 280 °C.
[0126] s) Free Fall Dart Determined according to ASTM D1709.
[0127] t) Film puncture Determined at 4.4 m / s, 23°C, according to ISO 7765-2.
[0128] u) Film tear test Determined according to ISO 6383-2.
[0129] v) Film tensile test Determined at 23°C according to ISO 527-3.
[0130] w) Glossy film exterior The measurements were performed at 45 degrees (inside of the film) according to ASTM D2457 on a 50 μm thick cast film produced on a monolayer cast film line with a melt temperature of 235°C and a cooling roll temperature of 20 to 60°C.
[0131] x) Transmittance, haze, transparency The measurements were carried out in accordance with ASTM D1003 on a 50 μm thick cast film produced on a monolayer cast film line with a melt temperature of 235° C. and a cooling roll temperature of 20 to 60° C.
[0132] 2. Working Example material IE1 and IE2 were pre-sorted by the polyolefin mechanical recycling process outlined above, including the quality control steps l1) / m1). For IE1, Swedish post-consumer plastic waste, rich in post-consumer flexible PP articles, was used as the precursor mixed plastic recycling stream (A). For IE2, German post-consumer plastic waste, meeting the standard DSD323-2, was used as the precursor mixed plastic recycling stream (A). For CE1, post-consumer plastic waste meeting the German standard DSD323-2 was used as the precursor mixed plastic recycling stream (A). However, the recycling process did not include a quality control step. CE2, CE3, CE4 (visbroken using peroxide), CE5, and CE6 are commercially available post-consumer recycles that were not pre-sorted further by the polyolefin mechanical recycling process outlined above, including the quality control steps l1) / m1).
[0133] As can be seen from Table 1, commercially available recyclates that have not been pre-sorted through the polyolefin mechanical recycling process outlined above, including quality control steps l1) / m1), do not fall within the claimed EPR range (<7.0 wt.%). Without being bound by any theory, it is hypothesized that these feedstocks are therefore not suitable starting materials for film production, as they do not address the challenges of conversion to film, such as polymer and melt homogeneity, and do not meet the mechanical performance requirements of the film.
[0134] [Table 1]
[0135] The PP material used has further properties outlined in Table 2. Cast films (50 μm) were produced from this polypropylene material using a melt temperature of 235°C and a screw speed of 95-100 rpm. Chill roll temperatures ranging from 20-60°C were used, depending on the polypropylene material used. Those skilled in the art will know the specific chill roll temperatures to select for a particular material. Film properties are also outlined in Table 2.
[0136] [Table 2(1)] [Table 2(2)] [Table 2(3)] [Table 2(4)] [Table 2(5)] [Table 2(6)]
[0137] It can be seen that the prior art is enhanced by the recycled compositions of the present invention. The feedstock of the present invention provides improved properties for the produced films, for example with respect to elasticity (see free-fall dart and film puncture). Furthermore, IE1 and IE2 provide improved optical properties (see clarity and haze).
Claims
1. A mixed plastic polypropylene blend comprising: (i) 900 to less than 924 kg / m 3 density determined according to DIN EN ISO 1183, (ii) a soluble fraction (SF) content, determined according to CRYSTEX QC analysis, ranging from 3.0 to 12.0 wt.%; having (iii) the soluble fraction (SF) has an ethylene-propylene rubber (EPR) content of formula (2) of less than 7.0% by weight, the EPR corresponding to a molar mass fraction of the soluble fraction (SF) in TCB at 35° C., obtained by cross fractionation chromatography (CFC) analysis, higher than 3.5 to 8 log M, [0010] where Hj represents the signal height at logM value j; (iv) the soluble fraction (SF) has an intrinsic viscosity (iV(SF)) in the range of 1.10 to less than 1.50 dl / g, preferably 1.25 to 1.45 dl / g; (v) said mixed plastic polypropylene blend has an inorganic residue measured by thermal analysis (TGA) according to DIN ISO 1172:1996 of 0.05 to 3.0 wt. %, preferably 0.05 to 2.5 wt. %, optionally 0.5 to 2.0 wt. %, based on said mixed plastic polypropylene blend; A mixed plastic polypropylene blend, wherein the mixed plastic polypropylene blend is a recycled material.
2. 2. The mixed plastic polypropylene blend of claim 1, wherein the ratio of the molecular weight of the low crystalline polyethylene fraction (LCF-PE) observed in the CFC analysis range of 60-85°C (Mw LCF(60-85)) to the molecular weight of the crystalline ethylene-propylene copolymer observed in the CFC analysis range of 103-109°C (Mw EP Copo(103-109)) is from 0.7 to less than 1.
4.
3. The low crystalline polyethylene fraction (LCF-PE) content represented by formula (5) is less than 7.0 wt%, preferably less than 6.0 wt%, and the LCF-PE content is obtained by CFC analysis; [0025] Hij represents the signal height, i represents the elution temperature, and j represents the logM value.
3. The mixed plastic polypropylene blend of claim 1 or claim 2.
4. having a large amplitude oscillatory shear-nonlinearity factor [LAOS-NLF] (190° C., 1000%) of greater than 1.5, preferably greater than 1.5 to 3.0, more preferably greater than 1.5 to 2.3; [0030] During the ceremony, G 1 ' is the first order Fourier coefficient, G 3 ' is the third order Fourier coefficient The mixed plastic polypropylene blend of any one of claims 1 to 3.
5. The mixed plastic polypropylene blend comprises: L of 30.0 to 90.0, preferably 35.0 to 71.0 * , -5.0 to 0.0 a * , b between 0.0 and 15.0 * CIELAB color space (L * a * b * 5. The mixed plastic polypropylene blend of claim 1, 2 or 3, wherein the blend comprises a carboxylic acid ester, ...
6. The mixed plastic polypropylene blend according to any one of claims 1 to 5, having a melt flow rate (ISO 1133, 2.16 kg; 230°C) of 1.0 to 100.0 g / 10min, preferably 2.0 to 20.0 g / 10min, more preferably 2.0 to 11.0 g / 10min, and most preferably greater than 2.0 to 10.0 g / 10min.
7. The following substances a) Polystyrene b) Polyamide-6 c) Limonene determined using solid phase microextraction (HS-SPME-GC-MS) d) Fatty acids determined using solid phase microextraction (HS-SPME-GC-MS) 7. The mixed plastic polypropylene blend of claim 1, further comprising one or more of:
8. 900-923kg / m 3 , preferably 905 to 922 kg / m 3 , more preferably 910 to 921 kg / m 3 , especially 915 to 920 mg / m 3 8. The mixed plastic polypropylene blend according to any one of claims 1 to 7, having a density, determined according to DIN EN ISO 1183, of 0.01 to 0.05%.
9. η(0.05 rad / s) of 2000 to 4300 Pa.s, preferably 2500 to 4000 Pa.s, in particular 3000 to 4000 Pa.s, at 200° C., and / or η(300 rad / s) of 200 to 280 Pa.s, preferably 210 to 275 Pa.s, in particular 240 to 270 Pa.s, at 200° C.
9. The mixed plastic polypropylene blend of any one of claims 1 to 8, having
10. The mixed plastic polypropylene blend according to any one of claims 1 to 9 having a shear thinning factor (STF), η(0.05) / η(300), of 9.5 to 16.0, preferably 10.0 to 14.
5.
11. 11. The mixed plastic polypropylene blend of any one of claims 1 to 10 in the form of pellets.
12. 12. An extruded article made from the mixed plastic polypropylene blend of any one of claims 1 to 11.
13. 13. The extruded article of claim 12 which is a film.
14. Use of the mixed plastic polypropylene blend according to any one of claims 1 to 11 for packaging.
Citation Information
Patent Citations
Polypropylene composition
CN111433277A
Crystalline polymer composition having low sealing temperature
JP1994025489A
Elastoplastic polyolefin composition
JP2002012715A
Propylene polymer composition
JP2013507497A
Method for producing polyolefin renewable materials
JP2019529191A